Cyberfenomenologi dan Evolusi Identitas Manusia Dalam Dunia Media Sosial: Pendekatan Studi Kualitatif - Rofiah, Chusnul (Develop, 2024)
This research explores users' subjective experiences in cyberspace through a cyberphenomenology approach, focusing on privacy, digital identity, and social interactions on social media. Using qualitative methods, data was collected through in-depth interviews and participant observation. Thematic analysis was applied to identify main themes related to freedom in building digital identities, concerns about the security of personal data, and the influence of social interactions on privacy behavior. This article also summarizes cyber phenomenology-based qualitative research procedures to serve as a guide for other researchers. The coding process was carried out using the color coding method, where each main theme is given a special color to facilitate grouping and manual analysis. The themes identified included flexibility in expressing digital identity, uncertainty regarding the use of personal data, and social pressure to share information. Findings show that many users feel freer in building their online identities, but face privacy risks due to a lack of digital literacy. Suggestions for digital platforms include providing more transparent privacy features and digital literacy education. Stricter privacy regulations are also needed to protect users in the digital era. This research provides important insights into the evolution of digital identity and the challenges faced in maintaining privacy on social media.